Relationship Between Education Level and Elderly Compliance in Hypertension Treatment in The Work Area of Datah Kotou Community Health Center - Triani, Rina; Tasalim, Rian; Rahman, Subhannur; Wijaksono, Muhammad (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension is a common health issue among the elderly, with prevalence increasing as age advances. According to data from the WHO, approximately 1.13 billion people worldwide suffer from hypertension, with the elderly being the most vulnerable group. Poor management of hypertension can lead to serious complications such as stroke, heart failure, and chronic kidney disease. Adherence to treatment is crucial to prevent these complications. However, many elderly individuals, especially those with low education levels, struggle to understand medical instructions and the importance of medication. This study aims to analyze the relationship between education level and adherence to hypertension treatment among the elderly in the working area of Puskesmas Datah Kotou, Puruk Cahu. Methods: This research employs a quantitative design with a cross-sectional approach. The sample consists of 30 elderly individuals diagnosed with hypertension, and data were collected through a questionnaire measuring education level and adherence using the Morisky Medication Adherence Scale (MMAS-8). Results: The results indicate that 83.3% of respondents have a low education level (elementary school), and 63.3% show low adherence to treatment. Statistical analysis reveals a significant relationship between education level and adherence, with a correlation coefficient of 0.691 and a p-value of 0.000. Conclusion: This study concludes that education level significantly affects the adherence of the elderly to hypertension treatment, highlighting the need for more effective health education interventions.